Karyotyping and in silico characterisation of the chromosomes of Diuraphis noxia (Hemiptera: Aphididae) - Steyn, Louis Johannes (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.